2019
DOI: 10.1177/2309499019850324
|View full text |Cite
|
Sign up to set email alerts
|

Addition of ceftaroline fosamil or vancomycin to PMMA: An in vitro comparison of biomechanical properties and anti-MRSA efficacy

Abstract: Background: Ceftaroline is a cephalosporin that is effective against methicillin-resistant Staphylococcus aureus (MRSA) infections. The objective of this study was to determine the feasibility of using ceftaroline-loaded Polymethyl methacrylate (PMMA) as antibiotic cement against MRSA versus vancomycin-loaded PMMA in an in vitro setting. Methods: PMMA pellets were prepared with three separate concentrations of each of the two antibiotics tested. They were tested to determine the effect of increasing concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…It was found that the resistance mechanism of vancomycin is mainly specific binding of vancomycinto the bacterial cell wall via peptidoglycan precursor small peptides, which are terminated with D-alanyl-D-alanine; this binding inhibits the elongation and cross-linking of bacterial cell wall peptidoglycans, thereby repressing cell wall synthesis and ultimately leading to bacterial death (Micek, 2007;Haseeb et al, 2019). However, the resistance of Staphylococcus aureus to vancomycin is increasing daily, causing widespread concern in the medical community (Haseeb et al, 2019 (Amberpet et al, 2019). VRSA refers to a minimal inhibitory concentration (MIC) of clinically isolated Staphylococcus aureus to vancomycin <32 mg/L, and was first reported in the United States in 2002.…”
Section: Vancomycinmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the resistance mechanism of vancomycin is mainly specific binding of vancomycinto the bacterial cell wall via peptidoglycan precursor small peptides, which are terminated with D-alanyl-D-alanine; this binding inhibits the elongation and cross-linking of bacterial cell wall peptidoglycans, thereby repressing cell wall synthesis and ultimately leading to bacterial death (Micek, 2007;Haseeb et al, 2019). However, the resistance of Staphylococcus aureus to vancomycin is increasing daily, causing widespread concern in the medical community (Haseeb et al, 2019 (Amberpet et al, 2019). VRSA refers to a minimal inhibitory concentration (MIC) of clinically isolated Staphylococcus aureus to vancomycin <32 mg/L, and was first reported in the United States in 2002.…”
Section: Vancomycinmentioning
confidence: 99%
“…These virulence factors are chiefly exotoxins that disrupt host cells, interfere with immune responses, and some proteins involved in adhesion and defense against host defenses (Kalia and Purohit, 2011;Yin et al, 2011). The expression of virulence factors is regulated by a complex network composed of multiple genes, of which agr a global regulatory factor H1, is the most important gene regulated by quorum sensing mechanisms (Haseeb et al, 2019). However, the inhibition of this quorum sensing mechanism in bacteria could result in the obstruction of biofilm formation, reduction in bacterial virulence and decreased bacterial resistance (Wang et al, 2017;Haseeb et al, 2019).…”
Section: Quorum Sensing Inhibitionmentioning
confidence: 99%
“…MRSA is not only resistant to β-lactam antibiotics, but also to other antimicrobial agents such as aminoglycosides, quinolones, and macrolides, and vancomycin has long been considered the first-line antibiotic treatment for invasive MRSA infection, including both HA-MRSA and CA-MRSA [ 18 ]. However the use of vancomycin has many shortcomings such as the slow bactericidal activity, high minimum inhibitory concentrations (MICs), reduced activity against biofilm-forming pathogens, and poor tissue penetration [ 19 ]. Several researchers [ 18 , 20 ] have shown that a subtherapeutic trough level of vancomycin is the main cause of treatment failure.…”
Section: Discussionmentioning
confidence: 99%
“…Vancomycin has long been considered the rst-line antibiotic treatment for invasive MRSA infection, including both HA-MRSA and CA-MRSA. However the use of vancomycin is limited because of its shortcomings such as the slow bactericidal activity, increased minimum inhibitory concentrations (MICs), reduced activity against bio lm-forming pathogens, and poor tissue penetration [22]. Several researchers have shown that subtherapeutic trough vancomycin concentration is the main reason of treatment failure.…”
Section: Discussionmentioning
confidence: 99%